Revenue Recognition Comparability and Analysts’ Disclosure Processing Costs - TILLET, ANDREA (Journal of Accounting Research, 2026)
ABSTRACT I examine whether the FASB's revenue recognition guidance under ASC 606 influences revenue comparability across firms and industries and whether revenue comparability reduces analysts’ disclosure processing costs. I extract firms’ revenue policy disclosures from 10‐K filings to measure their textual similarity and compare revenue policies across firms and industries. I find an increase in revenue comparability for firms in different industries with similar revenue‐generating transactions upon adoption of ASC 606. In contrast, I find a decrease in revenue comparability for firms in the same industry with similar revenue‐generating transactions. Further, though I find that analysts are more likely to forecast revenues when firms have higher revenue comparability, this benefit of revenue comparability is less pronounced under ASC 606. This finding suggests the ASC 606‐related changes to revenue comparability impose disclosure processing costs on analysts.